Improving Vocabulary Using Illustration For Fifth Year Students Of SD N Gendingan 4 Ngawi In 2011/2012 Academic Year - Widayanti, Anindita Puspa; , Dr. Anam Sutopo, M.Hum; , Nur Hidayat, S. Pd (2013)
This study aims at describing the procedures of teaching vocabulary using illustration and its influence to the students' vocabulary mastery and for clarifying the strengths and weaknesses of the illustration to teach vocabulary. The research was held in SD N Gendingan 4 Ngawi. The writer took 28 students of the fifth year as the subject. To collect the required data the writer compared the results of pre-test and post-test. We could see that improving vocabulary using illustration was able to achieve a good result. It means that the teaching-learning process was effective and successful. In pre-test the mean score was 64. 07, in post-test 1 the mean score was 80.46, and in post-test 2 the mean score was 83,89. It could be seen from the increasing result of students' achievement of the post-test 2 and was better than post-test 1. Post-test1 was better than pre-test.. It means that teaching vocabulary using illustration in SD N Gendingan 4 has a good result. The use of illustration in teaching vocabulary is very appropriate and helpful in teaching-learning process. The advantages of this research are the students have high interest in learning English and the students are motivated to be active in the class. The disadvantages of this research are the teacher needed much time to prepare material and she used the native language in the class.